Remarks on the deep-sea genus Pseudolamprops (Cumacea: Lampropidae) - Roccatagliata, Daniel; Mühlenhardt-Siegel, Ute (Zootaxa, 2012)
Based on two specimens collected in the Antarctic deep-sea (4928 m) the adult female and male of the genusPseudolamprops Gamô, 1989 are described for the first time. A new combination is proposed, Pseudolamprops profundus(Reyss, 1978) comb. nov., and several new records from the North Atlantic and Antarctica are provided. The diagnosis of Pseudolamprops is revised on the account of the new material available.